External Jugular Vein Vascular Malformation: Sonographic and MR Imaging Appearances - Ahuja, Anil T.; Yuen, Hok-Yuen; Wong, Ka-Tak; King, Ann D.; Abdullah, Victor; To, Edward; Chau, Yuk-Ping; Ma, Kwok-Fai (American Journal of Neuroradiology, 2004)
Summary: Vascular malformations arising from the wall of the external jugular vein are rare. This case series discusses the sonographic and MR imaging appearances of four such cases and reviews the literature. The diagnosis should be suggested preoperatively particularly because of the close relationship such malformations to the external jugular vein, as this helps surgeons to plan the operative procedure. The imaging appearances are similar to those of other vascular malformations elsewhere in the head and neck.